Investigating the impact of working arrangements and lifestyle factor importance on environmental consciousness - Andrew Chapman; Shamal Chandra Karmaker; Yosuke Shigetomi (Environmental Research Communications, 2023)
This study investigates the impact of people’s demographics, preferred working arrangements and utilization of their free time on environmental consciousness. Such an investigation is timely because of the changing expectations around working, and the rising popularity of work-from-home arrangements leading to increased flexibility. Although the link between income and environmental impact is well understood, the mediating factors between working arrangements and environmental concerns remain unclear. Through the analysis of a nationally representative survey conducted in Japan, we clarify people’s desire to work shorter hours, subject to the maintenance of income levels, along with a desire to consider revised working arrangements if environmental improvements can be anticipated as a result. One important finding of this research is that those who prioritize their free time for family and friends have a much higher probability of valuing the environment and thus reducing their carbon footprint. These findings have implications for policy design which encourages low impact working arrangements, the sharing economy and a family friendly society.